Visualizing the enzyme mechanism of mevalonate diphosphate decarboxylase - Chun-Liang Chen (Nature Portfolio, 2020)
Mevalonate diphosphate decarboxylase (MDD) is a key enzyme in the mevalonate pathway and catalyses the decarboxylation of mevalonate-5-diphosphate to isopentenyl diphosphate. Here, the authors provide insights into the conformational changes that occur during substrate binding of MDD and the subsequent enzymatic reaction steps by determining the substrate and intermediate bound crystal structures of Enterococcus faecalis MDD.